Family Nutrition: The Truth About Family Meals - Larry Forthun (EDIS)
FCS-8871, a 4-page fact sheet by Larry Forthun, summarizes recent research indicating the importance about family meals, including trends over the last several decades, effects on family togetherness, communication, well-being, and nutrition. Also discussed are family eating practices to avoid, and strategies for getting the whole family together for dinner. Includes references. Published by the UF Department of Family Youth and Community Sciences, September 2008.